The effect of brand heritage on brand loyalty mediated by brand image and brand trust on the viva cosmetics brand in West Sumatera - Aisyah, Nabila; Evanita, Susi (Marketing Management Studies, 2024)
The purpose of this study was to analyze The Influence of Brand Heritage on Brand Loyalty Mediated by Brand Image and Brand Trust on Viva Cosmetics Brand in West Sumatra. The population of the study were women domiciled in West Sumatra and had used Viva Cosmetics products for more than 2 years. The research sample was 250 respondents. Data were collected through online questionnaires and data analysis was carried out using Smart PLS software. The results of this study indicate that Brand Heritage and Brand Image have a significant positive effect on Brand Loyalty. Brand Trust does not have a significant effect on Brand Loyalty. Brand Heritage has a significant positive effect on Brand Image. Brand Heritage and Brand Image have a significant positive effect on Brand Trust. Brand Heritage has a significant positive effect on Brand Loyalty mediated by Brand Image. Brand Heritage has no significant effect on Brand Loyalty mediated by Brand Trust. Brand Heritage has a significant positive effect on Brand Trust mediated by Brand Image. Brand Heritage has no significant effect on Brand Loyalty mediated by Brand Image and Brand Trust. Brand Image has no significant effect on Brand Loyalty mediated by Brand Trust.